Go Green Around Campus: Environmental Management Collaboration With the Household Waste Disposal Association - Karmanah; Nia Sonani; Abdul Rahman Rusli; Dewi Fitrianti (Yayasan Almubarak Fil Ilmi, 2022)
Environmental management related to the handling of household waste in the RW 08 area is still shared homework. If not managed properly, the increasing number will cause problems, including environmental pollution, and affect public health problems. One of the efforts to reduce waste generation at Temporary and final Waste Disposal Sites, a Community Service activity (PKM), is carried out